2012
DOI: 10.1002/art.33407
|View full text |Cite
|
Sign up to set email alerts
|

75‐kd sirtuin 1 blocks tumor necrosis factor α–mediated apoptosis in human osteoarthritic chondrocytes

Abstract: Objective SirT1 has been previously implicated in the regulation of human cartilage homeostasis and chondrocyte survival. Exposing human osteoarthritic chondrocytes to TNFα generates a stable and enzymatically inactive 75kDa form of SirT1 (75SirT1) via Cathepsin B-mediated cleavage. Because 75SirT1 is resistant to further degradation, we assumed it has a distinct role in osteoarthritis (OA) pathology, which we sought out to identify in this study. Methods OA and normal human chondrocytes were analyzed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 49 publications
10
86
0
Order By: Relevance
“…1C, right panel). We previously showed that SIRT1 activity declines due to cleavage of the protein during OA pathogenesis and cartilage aging (Dvir‐Ginzberg et al ., 2011; Gabay et al ., 2012; Oppenheimer et al ., 2012). The cleavage of SIRT1 was also increased in DC compared with IC (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1C, right panel). We previously showed that SIRT1 activity declines due to cleavage of the protein during OA pathogenesis and cartilage aging (Dvir‐Ginzberg et al ., 2011; Gabay et al ., 2012; Oppenheimer et al ., 2012). The cleavage of SIRT1 was also increased in DC compared with IC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous reports provide another facet of regulation for SOX9, dependent on the decreased activity of SIRT1 seen with OA development (Dvir‐Ginzberg et al ., 2011; Gabay et al ., 2012; Oppenheimer et al ., 2012; Dvir‐Ginzberg & Steinmeyer, 2013). With advanced age and Inflammtory insult to the joint, SIRT1, the primary deacetylase of SOX9, becomes cleaved and inactivated, potentially leading to enhanced SOX9 acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…Because the levels of SIRT1 are reduced in human OA cartilage and chondrocytes (28,38), LEF1 levels are expected to be elevated in the affected tissue, with a corresponding elevation in MMP13. As predicted and shown in Fig.…”
Section: The Transcription Factor Lef1 Is a Transactivator Of Mmp13 Amentioning
confidence: 99%
“…Indeed, this report shows that SIRT1 reduced MMP13 gene expression and LEF1 protein levels in human primary chondrocytes. Furthermore, inflammation of the joint may lead to SIRT1 truncation (27), possibly reducing SIRT1 chromatin binding (28), sequentially lifting its inhibitory effects on LEF1 gene expression and promoting downstream MMP13 gene expression.…”
mentioning
confidence: 99%
“…This eventually leads impaired ECM synthesis, cartilage degradation and, ultimately, development of OA [36,37].…”
Section: Page 6 Of 39mentioning
confidence: 99%